CHARACTERIZATION OF A CHLORIDE CHANNEL IN THE INTERSTITIAL CELLS OF CAJAL - Mucci, Andrea (My University, 2004)
Interstitial cells of Cajal (ICC) are considered to be pacemaker cells, responsible for the maintenance of normal gastrointestinal (GI) motility. This functionality is achieved through spontaneous rhythmic inward currents related to the oscillating membrane potential, known as the slow wave. Chloride ions are thought to be one of the essential ions contributing to this periodic activity. However, the single-channel characteristics of the ion channel responsible for this ionic contribution remains to be modeled, and hence better understood, on the single-channel level. I show here single-channel evidence of the chloride channel previously shown to be involved in the pacemaking activity. Current-voltage analysis shows that the ion channel most likely has a unitary conductance of approximately 30pS. However, it is proposed that these channels exhibit positive cooperation, and hence are often found to open and close simultaneously, displaying conductance values that are multiples of their unitary conductance. A kinetic model is proposed based on Markov modeling. The channel has two stable open states and two stable closed states. A relatively long and a relatively short time constant are associated with each of these conducting states. This helps to account for the different kinetic modes observed in the channel behaviour. Carbachol is a drug that mimics acetylcholine, which is a neurotransmitter that the enteric nervous system is thought to use in order to modulate ICC activity. When the drug is given, the conductance values of the chloride channel in question increase drastically. This is hypothesized to be due to increased recruitment and cooperation of the channels. Furthermore, according to the single-channel kinetics, the model proposed for the control case models the channel in the presence of carbachol relatively well. The effects of carbachol can also be extended to propose a potential second messenger system (i.e., IP3) involved in the activation of the channel.
Keywords: Interstitial cells of Cajal; ICC; Cells; Single-channel; Carbachol